Synthesis of Consumer Society and Information Society - V. N. Leksin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
The first part of the article shows that modern consumer society, with all the fairness of its negative ethical assessments, has reduced the threat of overproduction of huge volumes of similar consumer goods and, at the same time, has stimulated the creation of new places of employment. This is justified by the data on the multiple expansion of the range of products and services demanded by the consumer. The second part of the article shows the most important foundations for the functioning of the information society, which ensured its expansion beyond corporate and national borders and transformation into a global phenomenon of our time. The unique role of the Internet in “mass digitalization”, in the formation of the “digital economy” and in the constant expansion of the consumer layer of its goods and services is analyzed. In the third part of the article, the organic and complementary combination of consumer society and information society features is called the information society of consumption.